Effect of Precursor Stoichiometry on the Performance and Stability of MAPbBr3 Photovoltaic Devices. Issue 4 (20th August 2019) - Falk, Lukas M.; Goetz, Katelyn P.; Lami, Vincent; An, Qingzhi; Fassl, Paul; Herkel, Jonas; Thome, Fabian; Taylor, Alexander D.; Paulus, Fabian; Vaynzof, Yana
Abstract : The wide‐bandgap methylammonium lead bromide perovskite is promising for applications in tandem solar cells and light‐emitting diodes. Despite its utility, there is a limited understanding of its reproducibility and stability. Herein, the dependence of the properties, performance, and shelf storage of thin films and devices on minute changes to the precursor solution stoichiometry is examined in detail. Although photovoltaic cells based on these solution changes exhibit similar initial performance, shelf storage depends strongly on precursor solution stoichiometry. While all devices exhibit some degree of healing, bromide‐deficient films show a remarkable improvement, more than doubling in their photoconversion efficiency. Photoluminescence spectroscopy experiments performed under different atmospheres suggest that this increase is due, in part, to a trap‐healing mechanism that occurs upon exposure to the environment. The results highlight the importance of understanding and manipulating defects in lead halide perovskites to produce long‐lasting, stable devices. Abstract : Herein, the effects of variations in precursor stoichiometry on the properties, performance, and stability of MAPbBr3 photovoltaic devices are examined. It is found that while the initial device performance is similar, devices with under‐stoichiometric composition are significantly improved upon storage in air without illumination, which is associated with defect healing.